(untitled) (Journal of Bio-Science, 2014)
Context: Puffer fish (Tetraodon patoca) contains a potent neurotoxin, tetrodotoxin (TTX) which specially blocks the voltage-gated sodium channels on the surface of nerve membranes. Although the fish as a diet produces sever toxicity in human but no such data are available on its nutrient contents. Mostly the poor people of our country some times eat this fish as a food and six peoples of a family died by its poisoning in Potuakhali, Bangladesh (2001). Our present data clearly indicated that the fish is a high source of oil and protein, and also significant amount of ash. Further, liver and head were the highest sources of toxin but dorsal and tail portion of the fish contained less amount of toxin Objectives: Compare the nutritional composition of different parts: Dorsal, Ventral including liver, Head and Tail of Puffer fish as well as analysis of their toxic properties. Materials and Methods: In this study, nutritional composition such as moisture, ash, protein, oil, polysaccharides, free sugar and mineral contents such as phosphorous, calcium and iron of four parts, namely Dorsal, Ventral including liver, Tail and Head of Puffer fish were analyzed by standard methods and toxic effects of its different parts were determined using brine shrimp lethality bioassay. Results: This study gives detailed information about the nutrients: moisture, ash, protein, oil, polysaccharides and free sugar content of four different parts (Dorsal, Ventral including liver, Tail and Head) of experimental fish which were explained in the result and discussion section. It can be concluded from the results that the puffer fish may be used as a good sources of oil, protein and minerals if proper precaution is taken to remove the toxin from different parts of the fish. In relation to toxicity against brine shrimp nauplii, the different parts of the fish can be arranged as follows-Liver >Head>Dorsal>Tail. Conclusion: The puffer fish might be used as a food due to its high content of oil, protein and minerals. Considering the toxicity, liver and head portion might be discarded completely, but the dorsal and the tail portion may be used due to its low toxicity DOI: http://dx.doi.org/10.3329/jbs.v20i0.17724 J. bio-sci. 20: 109-114, 2012